Beginner's luck - Clayborn, Kate (Clayborn, Kate. Chance of a lifetime romance., 2023)
"A scientist with a quiet, steady job at a university, Kit's focus has always been maintaining the acceptable status quo. A sudden windfall doesn't change that, with one exception: the fixer-upper she plans to buy, her first and only real home. It's more than enough to keep her busy, until an unsettlingly handsome, charming, and determined corporate recruiter shows up in her lab-and manages to work his way into her heart"--